Alexander, P.A. (2020). What research has revealed about readers’ struggles with comprehension in the digital age : moving beyond the phonics versus whole language debate. Reading Research Quarterly, 55(S1), S89– S97 - Capurro, Martina (2022)
Fil: Capurro, Martina. Pontificia Universidad Católica Argentina; Argentina